Międzywojenna proza Jarosława Iwaszkiewicza wobec problemu dewaluacji religii w Polsce początku XX wieku - Trubicka, Hanna (Polskie Towarzystwo Religioznawcze, 2012)
Hanna Trubicka – THE WORKS OF JAROSŁAW IWASZKIEWICZ IN THE PERIOD BETWEEN WWI AND WWII AND THE ISSUE OF DEVALUATION OF RELIGION IN POLAND AT THE BEGINNING OF THE 20TH CENTURY The article is an attempt to highlight the issue of secularization in the works of Jarosław Iwasz-kiewicz in the period between WWI and WWII. The slow vanishing of religion in the European and Polish culture in the first decades of the 20th century – interpreted by cultural criticism of those days as the vanishing of the universal sense making horizon – does affect the existential situation of reli-gious individuals, which remains the main objective of the Polish author. Iwaszkiewicz is interested in the processes of devaluation of religious values as far it is related to the insecurity felt by people and the awareness of arbitrariness of the choices made by them.